Early Oral Language Markers of Poor Reading Performance in Hong Kong Chinese Children - Liu, P.; McBride-Chang, C.; Wong, A.; Tardif, T.; Stokes, Stephanie; Fletcher, P.; Shu, H. (Sage Publications, Inc., 2010)
This study investigated the extent to which language skills at ages 2 to 4 years could discriminate Hong Kong Chinese poor from adequate readers at age 7. Selected were 41 poor readers (age M = 87.6 months) and 41 adequate readers (age M = 88.3 months). The two groups were matched on age, parents’ education levels, and nonverbal intelligence. The following language tasks were tested at different ages: vocabulary checklist and Cantonese articulation test at age 2; nonword repetition, Cantonese articulation, and receptive grammar at age 3; and nonword repetition, receptive grammar, sentence imitation, and story comprehension at age 4. Significant differences between the poor and adequate readers were found in the age 2 vocabulary knowledge, age 3 Cantonese articulation, and age 4 receptive grammar skill, sentence imitation, and story comprehension. Among these measures, sentence imitation showed the greatest power in discriminating poor and adequate readers.